2015
DOI: 10.4038/tar.v26i1.8078
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the Sri Lanka yellow dwarf coconut form as revealed by microsatellite markers

Abstract: ABSTRACT:Sri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The SSR markers developed based on this strategy include 296 validated SSR markers available at Tropgenedb (tropgenedb.cirad.fr). The SSR markers from this source have been frequently used in coconut genetic diversity studies 6 , 13 , 41 . Alternatively, with the advancement of next-generation sequencing, NGS-based approaches for identifying a large number of SSR loci have been proposed; for example, RNA sequencing (RNA-seq) analysis identified 6608 gene-based SSR loci from 57,304 unigenes 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR markers developed based on this strategy include 296 validated SSR markers available at Tropgenedb (tropgenedb.cirad.fr). The SSR markers from this source have been frequently used in coconut genetic diversity studies 6 , 13 , 41 . Alternatively, with the advancement of next-generation sequencing, NGS-based approaches for identifying a large number of SSR loci have been proposed; for example, RNA sequencing (RNA-seq) analysis identified 6608 gene-based SSR loci from 57,304 unigenes 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Dwarf coconuts are native to the Pacific region and cultivated worldwide, typically near human dwellings 1 . Tall coconut palms are predominately outcrossing and exhibit varying degrees of heterozygosity, while dwarf palms are normally self-pollinating and present higher levels of homozygosity, showing common morphological characteristics such as dwarf stature due to short internodes and slow growth of height, a slender trunk, a smaller crown, and large numbers of relatively small nuts with a low copra content 6 . Traditionally, genetic diversity assessment in coconut is based on morphological trait characterization and coconut breeding is performed through conventional methods, which are laborious, time consuming, and inefficient due to environmental factors and the limited number of phenotypic markers available 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Coconut ( Cocos nucifera L.) is a dioecious plant (2n = 2x = 32) with a haploid genome of approximately 2.4 Gb [ 1 , 2 , 3 ], which is native to the coastal regions of Melanesia and Southeast Asia [ 4 ]. According to plant morphology, coconuts can be divided into two subspecies: Cn.…”
Section: Introductionmentioning
confidence: 99%
“…In Sri Lanka, coconut has been classified into three varieties as Tall (Typica), Dwarf (Nana) and Intermediate (Aurantiaca), and under these three varieties 13 different forms of coconut were recognised by Liyanage (1958). Later, more forms were added into the varietal classification of coconut in Sri Lanka (Liyanage et al, 1988;Perera et al, 1997; December A recent study reported the morphological nonuniformity of the Sri Lanka Yellow Dwarf (SLYD) coconut population (Kamaral et al, 2014;Perera et al, 2015). Later, in addition to the pure SLYD, a new semi tall coconut phenotype was identified within this population bearing yellow coloured nuts.…”
Section: Introductionmentioning
confidence: 99%
“…The same studies revealed the presence of coconut phenotypes displaying mixed characters of SLYD and newly identified SLYST. In addition, molecular studies revealed the genetic variation of the coconut population bearing yellow colour coconuts in comparison to Sri Lanka tall, gon thembili tall and green dwarf as reference varieties (Kamaral et al, 2014;Perera et al, 2015).…”
Section: Introductionmentioning
confidence: 99%